The role of e-learning in enhancing digital thinking skills among university students - Al-Ghammaz, Saif Al-Deen; Alassaf, Hamzeh; Alsalti, Mahmoud; Almomani, Hana; Hleiban, Tahaweel (International Journal of Innovative Research and Scientific Studies, 2025)
This paper explores the role of e-learning in enhancing university students’ digital thinking skills. The descriptive approach is used. The research sample includes a sample of 120 male and female students randomly selected from the faculty of Arts at Al-Zaytoonah University of Jordan. The results indicate a medium degree of approval regarding digital thinking skills using e-learning in teaching. The research paper recommends furnishing students of the Faculty of Arts with digital training programs to enhance their digital skills and activate online learning programs in virtual classrooms. This paper enriches the Arab and Western libraries with original academic contributions and scholarship to knowledge about the significance of adopting digital thinking skills among students in daily life situations. Other key implications are reflected in activating electronic educational programs in virtual classrooms, developing educational programs specific to e-learning and encouraging teachers to use electronic curricula in e-learning. The paper recommends conducting a study on the effectiveness of e-learning in developing critical thinking skills, meta-digital thinking, advanced thinking skills, and meta-digital thinking skills regarding future research work. Conducting a study on enhancing digital learning abilities among pre-university and university students is one of the primary implications.